Growing cotton in Karshi Steppe, Uzbekistan: water productivity differences with three different methods of irrigation - Djumaboev, Kakhramon; Manthrithilake, Herath; Ayars, J.; Yuldashev, Tulkun; Akramov, Bekzod; Karshiev, R.; Eshmuratov, Davron (2019)
In Uzbekistan, generally practiced methods of irrigating crops are varieties of flooding (basin, border and furrow). These practices have created problems of waterlogging, salinity and lower irrigation efficiency. Waterlogging and salinization already affect 50 percent of irrigated areas, and irrigation efficiency hardly reaches up to 50-60%. The Karshi Steppe of Kashkadarya region is among the prime cotton and wheat producing areas in Uzbekistan, using around 4.5 – 5.0 billion m3 of irrigation water within a hydrological year. About 75% of this water is abstracted from Amu Darya River in the territory of Turkmenistan and raised up to 135 meters, using a cascade of seven pumping stations to Karshi main canal. Research on implications of applying other irrigation technologies with different irrigation regimes on cotton crop are limited in Uzbekistan, especially under water scarce situations, such as in Karshi Steppe. This study targeted that knowledge gap and compared performance of cotton crop under different irrigation regimes with three technologies (furrows, gated pipes, and drip). The yield data ranged from 3.5 to 4.6 t ha-1, whereas water productivity (WP) values ranged from 0.44 to 1.20 kg m-3 and irrigation water use efficiency (IWUE) ranged from 0.51 to 1.41 kg m-3. The measured ranges of IWUE and WP are much wider compared with data available for Karshi Steppe. Due to cotton being sensitive to soil-moisture stress, lack of skillful technicians at site for irrigation scheduling has led to more water stress than was planned for, resulting in lower crop yields than expected.